2006
DOI: 10.1007/s10439-006-9162-0
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided High-Intensity Focused Ultrasound for Conduction Block of Peripheral Nerves

Abstract: The objective of our work has been to investigate the use of ultrasound image-guided high-intensity focused ultrasound (HIFU) to non-invasively produce conduction block in rabbit sciatic nerves in vivo, a technique that could become a treatment of spasticity and pain. The work reported here involved the investigation of the duration of such conduction blocks after HIFU treatment and whether they resulted in axon degeneration. The right sciatic nerves of 12 rabbits were treated, under guidance of ultrasound ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 33 publications
4
58
1
1
Order By: Relevance
“…Several research groups have also reported that the modulation of neural activity is feasible through the application of short bursts of ultrasound pulses (1418), demonstrated by using a wide range of pulsing schemes having variations in duty cycle (DC), tone-burst duration (TBD), pulse-repetition frequency (PRF), sonication duration (SD), acoustic intensity (AI), and fundamental frequency (FF). On the other hand, continuous ultrasound waves have also been shown to modulate the brain neural activities (9, 1921); however, the question remains as to which one is more effective in achieving the desired modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have also reported that the modulation of neural activity is feasible through the application of short bursts of ultrasound pulses (1418), demonstrated by using a wide range of pulsing schemes having variations in duty cycle (DC), tone-burst duration (TBD), pulse-repetition frequency (PRF), sonication duration (SD), acoustic intensity (AI), and fundamental frequency (FF). On the other hand, continuous ultrasound waves have also been shown to modulate the brain neural activities (9, 1921); however, the question remains as to which one is more effective in achieving the desired modulation.…”
Section: Introductionmentioning
confidence: 99%
“…1,13,15,16 During the 1950s, high-intensity focused ultrasound (HIFU) was used experimentally to reversibly inhibit neuronal activity through moderate heating below the threshold for tissue ablation, 14 and it was used clinically to treat patients with movement disorders and brain tumors. 17,27 Advances in noninvasive, transcranial delivery of ultrasound over the past 15 years have renewed an interest in its use for neurosurgical applications.…”
mentioning
confidence: 99%
“…15,25,26,70,86 Other studies have demonstrated activation of neural tissue, both peripherally and in the CNS. 32,50,81 These effects have been postulated to occur as a result of mechanical stimuli (reversible) and thermal ablation (potentially irreversible).…”
Section: Neuromodulation and Epilepsymentioning
confidence: 99%